Correlation between energy efficiency in buildings and comfort of the users. (September 2017) - Reim, Michaela; Körner, Werner; Chhugani, Bharat; Weismann, Stephan
Abstract: The Energy Efficiency Center (EEC) is a reference building with innovative system components, a complex building control and a high degree of measuring and monitoring technology. During recent work, we investigated and optimized the control of the innovative daylighting and sun protection systems. The effectiveness of various optimization measures was confirmed by user surveys. Additional surveys allowed investigating the thermal comfort. Problems with thermal comfort seem to arise from the complex control of the regeneration of phase change materials embedded in the building. An optimization of this control is planned for some of the rooms.